PENGARUH KOMPENSASI, MOTIVASI, DAN DISIPLIN KERJA TERHADAP PRESTASI KERJA KARYAWAN PT ABC - RIZKY NANDA PRASETYA; ARIEF ALFIANDRY (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2021)
The purpose of this study was to determine the effect of compensation, motivation, and work discipline on work performance at PT Anugerah Setia Gas. The research design used in this study is descriptive and causal research. The sample used in the study was 60 employees using purposive sampling. Where the data collection technique is done using a questionnaire. Research data is processed with IBM statistics 25 as a tester. The results showed that compensation, motivation, and work discipline on the work performance of PT Anugerah Setia Gas employees. So that PT Anugerah Setia Gas needs to pay attention to compensation, motivation and work discipline in the workplace to obtain maximum employee performance